The Phenomenon of Trust in the Testaments of Moscow Grand Dukes in XIV Century - A. L. Korzinin (Управленческое консультирование, 2022)
The article is devoted to the investigation of the testaments of Moscow Grand Dukes in the XIV century, contains an analysis of the land holdings and the political role of the Grand Princesses. Based on the study of the testamentary acts of Ivan Kalita, Semyon Ivanovich, Ivan Ivanovich, Dmitry Ivanovich, the agreements of Simeon Gordy with brothers Ivan and Andrey, of Dmitry Donskoy with Vladimir Andreevich Serpukhovsky, the author reconstructs the system of distributing villages and volosts between princesses after the death of Moscow rulers. Discussion topics, related to the study of the composition of witnesses in the agreement of Semyon Ivanovich with his brothers, and the establishment of the identity of his uncle in the testament of Simeon Gordy are also considered.